Application of IR-radiometric diagnostics for control of vacuum connections of electrophysical installations - Prohorenko, E.M.; Klepikov, V.F.; Lytvynenko, V.V.; Bazaleyev, N.I.; Magda, I.I.; Prohorenko, T.G.; Morozov, A.I. (Вопросы атомной науки и техники, 2018)
The methods of IR-radiometric diagnostics of vacuum systems have been worked out. Several mechanisms are proposed that change the temperature field in the defect region. Depending on the type of defect, the main types of temperature anomalies are identified. The influence on the results of thermo graphic survey of such parameters as the assembly quality of the accelerator assemblies, the state of the material, and the cleanliness of the flange surface was studied. The possibility of detecting suction in case of a breach of air tightness of ducts is shown. To detect micro leakage of vacuum connections of the accelerator flanges, an IR-radiometric control is performed. Found leaks based on the received thermograms. They are found in the region of gas throttling or areas of variation in of the coefficient of radiation. Systematization of thermo images of defects in vacuum systems has been carried out. Systematized on the basis on the types of damage. Відпрацьовано методики ІЧ-радіометричної діагностики вакуумних систем. Запропоновано декілька механізмів, за рахунок яких змінюється температурне поле в області дефекту. Залежно від виду дефекту виділені основні прояви температурних аномалій. Вивчено вплив на результати термографічної зйомки таких параметрів: якості збірки вузлів прискорювача, стану матеріалу, чистоти поверхні фланців. Показана можливість виявлення підсосів у разі порушення герметичності повітроводів. Для виявлення мікротечі вакуумних з'єднань фланців прискорювача виконаний ІЧ-радіометричний контроль. Були знайдені течі на підставі отриманих термограм. Вони виявлені в області дроселювання газів або областях зміни коефіцієнта випромінювання. Проведена систематизація термозображень дефектів вакуумних систем на основі типів ушкоджень. Отработаны методики ИК-радиометрической диагностики вакуумных систем. Предложено несколько механизмов, в результате которых изменяется температурное поле в области дефекта. В зависимости от вида дефекта выделены основные проявления температурных аномалий. Изучено влияние на результаты термографической съемки таких параметров: качества сборки узлов ускорителя, состояния материала, чистоты поверхности фланцев. Показана возможность обнаружения подсосов в случае нарушения герметичности воздуховодов. Для обнаружения микротечей вакуумных соединений фланцев ускорителя выполнен ИК-радиометрический контроль. Были найдены течи на основании полученных термограмм. Они обнаружены в области дросселирования газов или областях изменения коэффициента излучения. Проведена систематизация термоизображений дефектов вакуумных систем на основе типов повреждений.